Pengaruh Media Pembelajaran Manik-Manik Bilangan terhadap Hasil Belajar Matematika Materi Operasi Hitung Penjumlahan Bilangan Cacah di Kelas II SDN Sikumana 2 - Melciana Timuneno; Ati, Chintia M.P. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning in elementary schools plays a crucial role in developing students’ numeracy competencies and conceptual understanding as foundational skills for higher-level mathematical thinking. However, many students continue to experience difficulties in understanding basic arithmetic operations, particularly whole-number addition, due to the abstract nature of mathematical concepts and the limited use of concrete learning media. This study aimed to examine the effect of number bead manipulatives on students’ mathematics learning outcomes in whole-number addition among second-grade students at SDN Sikumana 2, Kupang. The study employed a quantitative approach using a quasi-experimental design with a non-equivalent control group design. The participants consisted of 55 students, including 27 students in the experimental group and 28 students in the control group. Data were collected through pretest and posttest instruments and analyzed using descriptive statistics, normality tests, homogeneity tests, and independent samples t-test. The findings revealed that the mean score of the experimental group increased from 41.85 on the pretest to 81.67 on the posttest, while the control group improved from 40.54 to 55.54. The independent samples t-test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between the two groups. These findings demonstrate that number bead manipulatives significantly improve students’ mathematics learning outcomes by facilitating the transition from concrete experiences to symbolic representations, strengthening conceptual understanding, and supporting the development of foundational numeracy skills. The study contributes empirical evidence regarding the effectiveness of concrete manipulatives in elementary mathematics instruction and provides practical implications for designing developmentally appropriate numeracy learning environments